Imagens cinematográficas no cineclube como máquina de guerra : movimentos de pensamentos e criações curriculares - Fernandes, Nathan Moretto Guzzo (2019)
This is an invitation to sail. The text derives from research movements with cinematographic images, performed in the space of a movie club, located in a public school of the state school system in the city of Vitória/ES, where 24 meetings were held. It aims to accompany the aesthetic, ethical-political potentials and the movements of curricular inventions that are constituted by the networks of conversations, triggered with the cinematographic images exhibitions in the movie club. It presents a problematic field that explores the production/creation of thought and curriculum movements in the encounters with cinematographic images in the movie club. Dialogue with Deleuze (2013) and Machado (2009), to point out the set of image-times as the most powerful images to explore the senses and to move thought. It argues that the immanent processes of learning and teaching with films do not fit in a cliché form of display, indicating the power of aberrant forms in the film club to extrapolate what is foreseen in school curricula to create other relationships with images. It argues that the encounters with cinematographic images in the movie club, as coined by Deleuze and Guattari (2012), become a “war machine” in school daily life, which forces thought to nomadism and displacement, expands the processes of learning and teaching, creates other curricula and fables other modes of subjectivation in school. It uses cartography as a methodological tactic to accompany the inventive processes and production of subjectivity, engendered in the plane of life forces, based on Kastrup, Passos and Escóssia (2015); operates conversational networks as a micropolitical force to trigger narratives, supported by the ideas of Carvalho (2009). Bet on the notion of curricula in networks of affections, conversations and complex actions, woven into the school routine. It concludes that the cinematographic images in the movie club constitute like thinking machines - war machines - that create re-existences, which increases the strength of the school collective, inventing new/other curricula. As a product of the dissertation, Larrosa (2002) takes the notion of “experience” and unfolds it in an e-book, with reports of experiences of capixabas cineclubs, with which exposes clues to other ways of relating the cinema at school.